Attitudes of fourth and fifth grade students, towards the learning of mathematics - Jiménez Espinosa, Alfonso; Bohórquez Rodríguez, Hugo Hernán; Castro Torres, Marilú; Puentes Blanco, Rafael Antonio (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article is the result of an investigation that is carried out with fourth and fifth students of primary basic education, to identify causes that generate negative attitudes towards the learning of mathematics causing low academic performance, reflected in results of the Synthetic Index of Educational Quality (ISCE, 2015) by increasing the levels of insufficiency and decreasing the levels of advanced. The state of the art and the analysis of theoretical contributions related to attitudes are presented; positive and negative attitudes and attitudes towards mathematics and didactic strategies. The methodological process within the Research Action is described with a qualitative approach; using as instruments the questionnaires, narratives and participant observation. Among the initial results are aspects such as the need for greater dialogue between the teacher and their students and parents, to improve the discipline to avoid interference, to use manipulative materials and to carry out more non-traditional activities to improve the classroom environment.